Brainwave entrainment to minimise sedative drug doses in paediatric surgery: a randomised controlled trial. (September 2020) - Schmid, Werner; Marhofer, Peter; Opfermann, Philipp; Zadrazil, Markus; Kimberger, Oliver; Triffterer, Lydia; Marhofer, Daniela; Klug, Wolfgang
Abstract: Background: Anaesthetic drugs may cause neuroapoptosis in children and are routinely used off-label in specific age groups. Techniques that reduce anaesthetic drug dose requirements in children may thus enhance the safety of paediatric sedation or anaesthesia. Brainwave entrainment, notably in the form of auditory binaural beats, has been shown to have sedative effects in adults. We evaluated the influence of brainwave entrainment on propofol dose requirements for sedation in children. Methods: We randomised 49 boys scheduled for sub-umbilical surgery under caudal blockade to an entrainment or a control group. Small differences in pitch were applied to each ear to create binaural beats, supplemented by synchronous visual stimuli, within the electroencephalographic frequency bands seen during relaxation and (rapid eye movement/non-rapid eye movement) sleep. After establishment of caudal block, propofol infusion was started at 5 mg kg −1 h −1 . Intraoperatively, the infusion rate was adjusted every 5 min depending on the sedation state judged by the bispectral index (BIS). The infusion rate was decreased by 1 mg kg −1 h −1 if BIS was <70, and was increased if BIS was >70, heart rate increased by 20%, or if there were other signs of inadequate sedation. Results: Mean propofol infusion rates were 3.0 (95% confidence interval [CI]: 2.4–3.6) mg kg −1 h −1 vs 4.2 (95% CI: 3.6–4.8) mg kg −1 h −1 in the entrainment and control groups, respectively ( P <0.01). BIS values were similar in the two groups. Conclusions: Brainwave entrainment effectively reduced the propofol infusion rates required for sedation in children undergoing surgery with regional anaesthesia. Further studies are needed to investigate the possibility of phasing out propofol infusions completely during longer surgical procedures and optimising the settings of brainwave stimulation. Clinical trial registration: DRKS00005064.